Innovating a meaningful gamified instruction: an instructor's quest to fulfil the demands of 21st century learners - Md. Khambari, Mas Nida (Asia-Pacific Society for Computers in Education, 2016)
In the quest to fulfill the demands of 21st Century Learners who are digital citizens, this study aims to explore the gamified instruction approach in the context of higher education institution and how it could impact learning and instruction. The dynamic and adaptive nature of today learners calls for a new mode of instruction–bringing new challenges to instructors. This study is deemed timely in the transformation age of instructional system. It also echoes the Malaysian Education Ministry aspirations to become world’s leading education system that actively pursue technologies and innovations that fulfil 21st Century learners’ needs and enables greater personalization of learning experience.